Empowering Village Women through Circular Economy: Transformation of Organic Waste into Eco-friendly Biopesticide in Ulak Segelung Village - Selpiana Selpiana; Nina Haryani; Tine Aprianti; Nyimas Ulfatry Utami (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This research aims to empower village women in Ulak Segelung Village through a circular economy approach by transforming organic waste into environmentally friendly biopesticides. Local communities face the dual challenges of high levels of unmanaged household organic waste, farmers' dependence on synthetic chemical pesticides, and women's low economic independence. Using a participatory empowerment model, the program involved 30 homemakers in hands-on training of EM Bokashi anaerobic fermentation technology. The program's effectiveness was evaluated using a One-Group Pretest-Posttest design. The results showed significant improvements in participants' capacity; technical knowledge increased from 48% to 86%, and practical skills rose from 40% to 82%. Environmentally, the initiative increased organic waste collection by 175% (from 8 kg to 22 kg/week). The biopesticide produced (25 liters/week) showed 55% efficacy in reducing pest intensity in local farmlands. Economically, the establishment of the Women's Business Group successfully commercialized the product with 87.5% sales growth in the second month. The study concluded that the program succeeded in creating a circular economy model that reduces environmental pollution while providing a new independent source of income for village women. The study recommended standardizing product legality and expanding market networks. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 5: Gender EqualitySDG 12: Responsible Consumption and ProductionSDG 15: Life on Land